The saffron kitchen - Crowther, Yasmin (London Abacus, 2007)
A passionate novel about mothers and daughters, roots and exile, set among an Anglo-Iranian family.
First published in Great Britain in 2006 by Little, Brown.
UCWS-3365g donated by Adrienne Maguddayao - August 2019
Keywords: Mothers and daughters -- Fiction; Iranians -- England -- London -- Fiction; Exiles -- Fiction; London (England) -- Fiction; Domestic fiction